Anatomical study with Antibacterial and Antibiofilm Effects of Erodium cicutarium (L.) L'H Phenolic Roots Extract - Zubaida A. Lattef Ismaeel (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Bacteria acquire resistance to antibacterial drugs,so there is always a need for new drugs to inhibit many human bacterial pathogens. Novel studies were carried out to study the internal structures as well as the antibacterial effect of Erodium cicutarium phenolic root extracts (APR) on the development of biofilm formation of bacterial species (Klebsiella pneumoniae) and (Staphylococcus aureus) using four strains from both clinical and environmental samples In-Vitro. Anatomy of all the vegetative parts showed a presence of tannin filled cells in their structures. Also, the experiments were conducted to study the antibacterial effect by determining the minimum inhibitory concentrations (MICs), and susceptibility test of these strains for five antibiotics. Although the APR concentrations (50, 25, 12.5, 6.25, 3.125, and 1.625 μg/ml) (W/V) were used through antibiotic and biofilm inhibition assay. The result of sensitivity test showed more resistant to various antimicrobial especially Amoxicillin, Cephalothin and Methicillin for both bacteria strains. Also, among the MICs tested, showed that the ranged value was in concentration between 0.017 to 0.650 mg/ml for both K. pneumoniae and S. aureus strains. Furthermore, biofilm reduction assay results for treatments showed that the highest activity was obtained with phenolic root extracted, biofilm eradication at 1.3 mg/ml. In conclusion, the results showed that relatively low concentrations of phenolic root extracts displayed promising antibacterial and antibiofilm capabilities making them attractive for additional studies as “novel therapeutic agents.”